Apache II scoring in predicting surgical outcome in patients of perforation peritonitis - Agarwal, Anand; Choudhary, Ganpat Singh; Bairwa, Mansingh; Choudhary, Amit (International Surgery Journal, 2017)
Background: Many scoring systems have been found useful in predicting the outcome in critically ill patients, amongst them acute physiology and chronic health evaluation score (APACHE II) appeared to be the most widely used and had a general acceptance in assessing the critically ill patients, for its easy applicability and ability to predict outcome. Methods: To predict the surgical outcome in patients of perforation peritonitis APACHE II scoring done in every diagnosed case of perforation peritonitis in a prospective study from January 2015 to June 2016 was done. 100 patients with perforation peritonitis fulfilling the inclusion and exclusion criterion underwent exploratory laparotomy in Mahatma Gandhi hospital, Dr. S.N. Medical college, Jodhpur, Rajasthan, India. Results: In current study, 69 patients were in the low risk group (apache score 0-5) and 24 patients were in the medium risk group (Apache score 6-10) and 7 patients were in the high-risk group (Apache score 11-16). Of these 100 % patients in low risk group and 95.8% patients in medium risk group were discharged in satisfactory manner and 100% patients expired in high risk group. Conclusions: APACHE II score correlated well with the outcome in current study, it also correlated well with the hospital and ICU stay.